2019
DOI: 10.3389/fmicb.2019.01797
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing of Extended-Spectrum Beta-Lactamase (ESBL)-Producing Escherichia coli Isolated From a Wastewater Treatment Plant in China

Abstract: Background and Objectives Wastewater treatment plants (WWTPs) are one of the major reservoirs for antimicrobial resistant bacteria (ARB) and antimicrobial resistance genes (ARGs) in the environment. Thus, the investigation on ARB and ARGs from WWTPs has attracted increasing attention in recent years. In order to uncover the resistome in a WWTP treating effluents from a pharmaceutical industry in China, the extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…A huge diversity of virulence genes often associated with pathogenic E. coli was found in the genomes of isolates in this study ( Table 1). Similar virulence factors have been identified in environmental E. coli isolates obtained from surface water and WWTPs in previous studies (8,36). Most virulence genes were associated with the insertion sequences, suggesting that these are important in the mobilization of the bacterial virulome ( Table 4).…”
Section: Discussionsupporting
confidence: 79%
“…A huge diversity of virulence genes often associated with pathogenic E. coli was found in the genomes of isolates in this study ( Table 1). Similar virulence factors have been identified in environmental E. coli isolates obtained from surface water and WWTPs in previous studies (8,36). Most virulence genes were associated with the insertion sequences, suggesting that these are important in the mobilization of the bacterial virulome ( Table 4).…”
Section: Discussionsupporting
confidence: 79%
“…The T3SS effector leucine-rich repeat protein EspR1 was present in strains NMBU_ W12E19 and NMBU_ W13E19, while only strain NMBU_W13E19 was positive for the EspR2 protein. Strain NMBU_W13E19 displayed the gene combination eilA, Air and lpfA (encoding for long polar fimbriae) that was recently reported from a bla CTX−M -producing E. coli strain isolated from a wastewater treatment plant in China (Jiang et al, 2019) and in eight food-producing animal isolates (seven turkey and one laying hen) in Poland (Zajac et al, 2019). This particular gene combination was also seen in the first clinical isolate of an E. coli harboring the mcr-1 gene in Mexico, isolated in 2017 (Merida-Vieyra et al, 2019), as well as in six ESBL-producing E. coli strains isolated from veterinary hospital staff and students in three United Kingdom veterinary hospitals (Royden et al, 2019).…”
Section: Detection Of Virulence Factorsmentioning
confidence: 94%
“…In our previous study, we obtained several ESBLproducing E. coli strains from a WWTP located in Taizhou, Zhejiang province, China. 9 This WWTP treats the wastewater from a pharmaceutical company which produces antimicrobial agents including beta-lactam antibiotics such as cefaclor, ceftizoxime, ceftibuten, cefuroxime sodium, cefprozil, cefdinir, and cefixime. Here, we reported the isolation of another strain, E. coli strain R15, from this WWTP.…”
mentioning
confidence: 99%
“…The isolation and identification of R15 was performed as described previously. 9 Antimicrobial susceptibility testing by VITEK 2 Compact (bioMérieux, France) showed that R15 was resistant to various types of antimicrobial agents, including ampicillin (MIC ≥ 32 μg/mL), amoxicillin (MIC ≥32 μg/ mL), piperacillin (MIC ≥ 128 μg/mL), cefazolin (MIC ≥ 64 μg/mL), cefoxitin (MIC ≥ 64 μg/mL), ceftriaxone (MIC ≥ 64 μg/mL), cefepime (MI C≥ 64 μg/mL), ertapenem…”
mentioning
confidence: 99%